Polyethylene powder and moldings

By controlling the slope of the torque curve during the mixing process of polyethylene powder, polyethylene powder with high shutdown function and excellent long-term stability was prepared, and the shutdown function and long-term stability of the battery separator in the prior art was solved. Deficiencies in the aspects.

CN116508203BActive Publication Date: 2025-02-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202180073262.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-17
Filing Date
2021-11-12
Publication Date
2025-02-25
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

There is still room for improvement in the shutdown function and long-term stability of existing polyethylene resin compositions, especially in the applications of separators for batteries.

Method used

When kneading under predetermined kneading conditions, the slope of the straight line connecting two extreme points in the torque curve is more than 2N·m/min and less than 15N·m/min, and the viscosity average molecular weight is more than 100,000. And polyethylene powder below 2,500,000.

Benefits of technology

A microporous membrane for batteries with excellent appearance, high shutdown function and excellent long-term stability is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116508203B_ABST
    Figure CN116508203B_ABST
Patent Text Reader

Abstract

A polyethylene powder, wherein the viscosity average molecular weight of the polyethylene powder is 100,000 or more and 2,500,000 or less, and in the torque curve obtained when mixing under the following <mixing conditions> using a laboratory mixing extruder, the slope of the straight line connecting two maximum points is 2 N·m / min or more and 15 N·m / min or less. <Mixing conditions> Using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), 24 g of liquid paraffin is mixed for 10 minutes at a set temperature of 114°C and a rotation speed of 5 rpm, then 16 g of the polyethylene powder and 0.4 g of an antioxidant are added, the rotation speed is adjusted to 30 rpm and mixed for 3 minutes, and then the set temperature is raised from 114°C to 163°C in 1 minute. After the temperature is raised, mixing is performed for 5 minutes at a set temperature of 163°C and a rotation speed of 30 rpm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polyethylene powder and shaped bodies. Background Art

[0002] Ultra-high molecular weight polyethylene powder has been formed by various molding methods such as melt stretching, injection molding, extrusion molding, and compression molding, and has been used for various purposes such as films, sheets, microporous films, fibers, foams, and tubes. In recent years, the demand for microporous films has grown rapidly, and the microporous films are used as separators that are important components of lithium-ion batteries, lead-acid batteries, etc.

[0003] In addition to the function of isolating the positive and negative electrodes while allowing only ions to pass through, battery separators also have a shutdown function for preventing battery reaction runaway by partially melting the pores when a large current flows, that is, a function of blocking the pores at a temperature lower than the temperature of thermal runaway, the so-called fuse effect, and it is required to improve this shutdown function.

[0004] In addition, battery separators are required to have high mechanical strength.

[0005] In addition, in the manufacture of battery separators, a wet extrusion method is generally used in which polyethylene powder is dissolved in a solvent and extruded. During the extrusion of the polyethylene powder, when the dispersibility of the polyethylene powder in the solvent is poor, unmelted material is produced, resulting in clogging of the filter of the extruder and deterioration of the appearance of the separator. Therefore, in order to improve the appearance, it is required to improve the dispersibility of the polyethylene powder in the solvent.

[0006] In recent years, the demand for higher capacity and higher output has been rapidly increasing, especially for automotive batteries. Along with this, battery separators are required to have further improvements in long-term stability and shutdown function.

[0007] Here, the long-term stability of the battery separator means that the ion permeability does not vary due to the uniform pore structure of the microporous membrane, and short circuits and time-dependent degradation are unlikely to occur.

[0008] Patent Document 1 discloses a polyethylene resin composition containing an ethylene homopolymer and having a specific melt flow rate, a specific molecular weight distribution, and a specific elution amount measured by cross-fractionation chromatography as a polyethylene resin composition capable of obtaining a microporous film having excellent processability, air permeability, and mechanical strength.

[0009] Patent Document 2 discloses a battery separator that includes three types of polyethylene having different physical properties and has a low shutdown temperature and certain membrane strength and gas permeability.

[0010] Patent Document 3 discloses a battery separator having excellent long-term storage properties, a high yield, and high output characteristics.

[0011] Patent Document 4 discloses a technique for simultaneously imparting a predetermined particle size distribution and a predetermined swelling ratio as a technique for obtaining a polyethylene powder having excellent solubility and capable of improving productivity and product quality in processing and molding, particularly in wet extrusion molding.

[0012] In addition, Patent Document 5 discloses a polyethylene resin composition produced by multi-step polymerization and a molded product thereof, wherein the polyethylene resin composition has excellent moldability, durability and impact strength, and when formed into a molded product, it is not easy to produce bumps and depressions caused by high molecular weight gel, and it is possible to produce a molded product with excellent appearance.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent No. 5840743

[0016] Patent Document 2: Japanese Patent No. 5722305

[0017] Patent Document 3: Japanese Patent No. 6135665

[0018] Patent Document 4: Japanese Patent Application Publication No. 2019-19265

[0019] Patent Document 5: Japanese Patent No. 6281372 Summary of the invention

[0020] Problems to be solved by the invention

[0021] However, the polyethylene resin composition described in Patent Document 1 has the following problems: although it is excellent in mechanical strength, air permeability and processability, there is still room for improvement in shutdown function and long-term stability.

[0022] In addition, in Patent Document 2, no research has been conducted to improve the dispersibility of the resin in the extrusion solvent, and there is a problem that the component with the highest molecular weight may remain in the microporous membrane as an unmelted product, thereby causing a problem of poor appearance. In addition, in the microporous membrane, the entanglement of the molecular chains is strong at the part where the components with high molecular weight are concentrated, so local shrinkage is likely to occur, and the pore structure of the microporous membrane becomes uneven, so the permeation of ions is biased, and there is a problem of poor long-term stability.

[0023] Furthermore, Patent Document 3 has a problem in that no research has been conducted on improving the shutdown function of the battery separator.

[0024] In addition, Patent Documents 4 and 5 have the problem that no research has been conducted on improving the long-term stability and shutdown function of the battery separator.

[0025] Therefore, in view of the above-mentioned problems of the prior art, the present invention aims to provide a polyethylene powder capable of obtaining a microporous membrane for a battery separator having excellent appearance, high shutdown function and excellent long-term stability due to a uniform pore structure.

[0026] Means used to solve problems

[0027] The present inventors conducted intensive research to solve the above-mentioned problems and found that by specifying the slope of the straight line connecting the two maximum points in the torque curve obtained when kneading is carried out under predetermined kneading conditions, a polyethylene powder that can solve the above-mentioned problems can be obtained, thereby completing the present invention.

[0028] That is, the present invention is as follows. [1]

[0030] A polyethylene powder having a viscosity average molecular weight of 100,000 or more and 2,500,000 or less, wherein:

[0031] In the torque curve obtained when kneading was performed using a laboratory kneading extruder (Labo Plastomill) under the following <kneading conditions>,

[0032] The slope of the straight line connecting the two maximum points is greater than 2 N·m / min and less than 15 N·m / min,

[0033] <Mixing conditions>

[0034] Using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), 24g of liquid paraffin was mixed for 10 minutes at a set temperature of 114°C and a rotation speed of 5rpm, then 16g of the polyethylene powder and 0.4g of an antioxidant were added, the rotation speed was adjusted to 30rpm and mixed for 3 minutes, and then the set temperature was raised from 114°C to 163°C in 1 minute; after the temperature was raised, mixing was performed for 5 minutes at a set temperature of 163°C and a rotation speed of 30rpm. [2]

[0036] The polyethylene powder as described in the above [1], wherein, in a torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder,

[0037] Mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.3. [3]

[0039] The polyethylene powder according to the above [1] or [2], wherein, in a torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder,

[0040] Mixing energy at the beginning of swelling (E 0 ) is the total mixing energy (E t ) is less than 5%. [4]

[0042] The polyethylene powder according to any one of [1] to [3] above, wherein, in a torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder,

[0043] Mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.1. [5]

[0045] The polyethylene powder according to any one of [1] to [4] above, wherein the polyethylene powder has a median particle size of 50 μm or more and 250 μm or less. [6]

[0047] The polyethylene powder according to any one of [1] to [5] above, wherein the polyethylene powder is used for a battery separator. [7]

[0049] A molded product, wherein the molded product is a molded product of the polyethylene powder according to any one of [1] to [5] above. [8]

[0051] The molded article as described in the above-mentioned [7] is a microporous membrane. [9]

[0053] The molded article according to the above-mentioned [7] or [8], wherein the molded article is a battery separator.

[0054] Effects of the Invention

[0055] According to the present invention, there can be provided a polyethylene powder capable of obtaining a microporous membrane that is excellent in appearance, has a high shutdown function, and has excellent long-term stability as a battery separator due to having a uniform pore structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 An example of a torque curve of polyethylene powder is shown. DETAILED DESCRIPTION

[0057] Hereinafter, a mode for carrying out the present invention (hereinafter also referred to as “the present embodiment”) will be described in detail.

[0058] It should be noted that the following embodiments are examples for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be implemented with various modifications within the scope of the gist of the invention.

[0059] [Polyethylene powder]

[0060] The viscosity average molecular weight of the polyethylene powder of this embodiment is 100,000 or more and 2,500,000 or less, and

[0061] In the torque curve obtained when kneading is performed under the following <kneading conditions> using a laboratory kneading extruder, the slope of a straight line connecting two maximum points is 2 N·m / min or more and 15 N·m / min or less.

[0062] <Mixing conditions>

[0063] Using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), 24 g of liquid paraffin was mixed for 10 minutes at a set temperature of 114° C. and a rotation speed of 5 rpm, then 16 g of the above-mentioned polyethylene powder and 0.4 g of an antioxidant were added, the rotation speed was adjusted to 30 rpm and mixed for 3 minutes, and then the set temperature was raised from 114° C. to 163° C. in 1 minute. After the temperature was raised, mixing was performed for 5 minutes at a set temperature of 163° C. and a rotation speed of 30 rpm.

[0064] The polyethylene powder of the present embodiment has the above-mentioned configuration, and thus can provide an effect of obtaining a microporous membrane for a battery separator that has excellent appearance, high shutdown function, and excellent long-term stability due to having a uniform pore structure.

[0065] The long-term stability of a battery separator means that the microporous membrane has a uniform pore structure and thus has no deviation in ion permeability, and is not prone to short circuits or time-dependent degradation.

[0066] Hereinafter, the structure of the polyethylene powder according to the present embodiment will be described.

[0067] The polyethylene powder (hereinafter sometimes simply referred to as “powder”) of the present embodiment is composed of an ethylene-based polymer.

[0068] Examples of ethylene-based polymers include ethylene homopolymers and copolymers of ethylene and other comonomers copolymerizable with ethylene (for example, binary or ternary copolymers). The bonding form of the copolymer may be random or block.

[0069] The other comonomers copolymerizable with ethylene are not particularly limited, and examples thereof include α-olefins, vinyl compounds, etc. The other comonomers may be used alone or in combination of two or more.

[0070] There are no particular restrictions on the α-olefins, and examples thereof include α-olefins having 3 to 20 carbon atoms, and specifically include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, etc. Among them, as other comonomers, propylene and / or 1-butene are preferred from the viewpoint of further improving the heat resistance and strength of the microporous membrane.

[0071] The vinyl compound is not particularly limited, and examples thereof include vinylcyclohexane, styrene, and derivatives thereof.

[0072] Furthermore, as other comonomers, non-conjugated polyenes such as 1,5-hexadiene and 1,7-octadiene may be used as necessary.

[0073] (Viscosity average molecular weight (Mv))

[0074] The viscosity average molecular weight (Mv) of the polyethylene powder of the present embodiment is 100,000 or more and 2,500,000 or less, preferably 200,000 or more and 2,000,000 or less, and more preferably 250,000 or more and 1,200,000 or less.

[0075] The viscosity average molecular weight (Mv) of the polyethylene powder can be controlled within the above numerical range by appropriately adjusting the polymerization conditions described below, etc. Specifically, the viscosity average molecular weight (Mv) can be controlled by allowing hydrogen as a chain transfer agent to exist in the polymerization system or by changing the polymerization temperature, etc.

[0076] The viscosity average molecular weight (Mv) of the polyethylene powder is 100,000 or more, and the microporous membrane including the polyethylene powder of the present embodiment has sufficient mechanical strength. On the other hand, the viscosity average molecular weight (Mv) is 2,500,000 or less, and the polyethylene powder of the present embodiment has excellent molding processability such as dispersibility and stretchability in a solvent. Therefore, the microporous membrane molded using the polyethylene powder of the present embodiment has less unmelted matter and uneven thickness, and has an excellent appearance.

[0077] The viscosity average molecular weight (Mv) of the polyethylene powder of the present embodiment can be calculated by the following formula from the intrinsic viscosity [η] (dL / g) determined in accordance with ISO 1628-3 (2010). More specifically, it can be measured by the method described in Examples.

[0078] Mv=(5.34×10 4 )×[η] 1.49

[0079] (The slope of the straight line connecting two maximum points in the torque curve)

[0080] Known indicators for estimating the permeability of the plasticizer into the polyethylene powder include the pore properties of the powder and the solubility under static conditions.

[0081] However, since mechanical external force is applied to the polyethylene powder and the plasticizer during the molding process, there is a possibility that the impregnation properties estimated from the above-mentioned indexes and the actual impregnation properties may differ.

[0082] One of the biggest factors that determine the physical properties of a microporous membrane formed using polyethylene powder is the entanglement of polyethylene molecular chains formed during extrusion. The entanglement of the molecular chains can be accurately evaluated using indicators under specified extrusion conditions.

[0083] Therefore, in this embodiment, in order to identify polyethylene powder suitable for microporous membranes, the slope of the straight line connecting two maximum points in the torque curve obtained under predetermined mixing conditions is specified, thereby simultaneously and accurately evaluating the permeability of the plasticizer into the polyethylene powder and the physical properties of the microporous membrane.

[0084] That is, it was found that in the torque curve obtained when the polyethylene powder of this embodiment was mixed under the following <mixing conditions> using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), the slope of the straight line connecting the two maximum points was greater than 2 N·m / minute and less than 15 N·m / minute, thereby obtaining a polyethylene powder that is very suitable as a raw material for a microporous membrane.

[0085] exist Figure 1 An example of the above torque curve is shown in FIG.

[0086] exist Figure 1 In the graph, the average torque (rotational load generated during kneading) (N·m) when kneading is performed under predetermined kneading conditions is shown on the vertical axis, and the kneading time (minutes) is shown on the horizontal axis. It should be noted that the solid line represents the average torque, and the dotted line represents the set temperature.

[0087] <Mixing conditions>

[0088] Using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), 24 g of liquid paraffin was mixed for 10 minutes at a set temperature of 114° C. and a rotation speed of 5 rpm, then 16 g of the above-mentioned polyethylene powder and 0.4 g of an antioxidant were added, the rotation speed was adjusted to 30 rpm and mixed for 3 minutes, and then the set temperature was raised from 114° C. to 163° C. in 1 minute. After the temperature was raised, mixing was performed for 5 minutes at a set temperature of 163° C. and a rotation speed of 30 rpm.

[0089] In the torque curve obtained when the polyethylene powder of this embodiment is kneaded under the above-mentioned <mixing conditions>, the slope of the straight line connecting the two maximum points is in the range of 2 N·m / minute to 15 N·m / minute, preferably in the range of 3 N·m / minute to 12 N·m / minute, and more preferably in the range of 5 N·m / minute to 10 N·m / minute.

[0090] By setting the slope of the straight line connecting the two maximum points in the torque curve obtained when kneading under the above <kneading conditions> to be 2 N·m / min or more, the generation of unmelted matter can be suppressed, and there is a tendency to manufacture a microporous membrane with excellent appearance. In addition, by setting the above slope to be 2 N·m / min or more, the state of uneven entanglement of molecular chains in the polyethylene powder can be made uniform, so the microporous membrane obtained by molding the polyethylene powder of this embodiment has a uniform pore structure and tends to have excellent long-term stability.

[0091] On the other hand, when the slope is 15 N·m / min or less, the fluidity of the polyethylene in the melt becomes good, and there is a tendency that a microporous membrane in which pores are easily blocked during shutdown can be produced.

[0092] Usually, polyethylene powder has many holes. When extrusion processing is performed in a plasticizer, the plasticizer infiltrates into the polyethylene powder from these holes. At this time, when there is a pore structure that is not easy to be infiltrated by the plasticizer, before the plasticizer infiltrates into the center of the polyethylene powder, the temperature of the polyethylene powder reaches above the melting point and begins to melt, resulting in pore occlusion. The dispersibility of the center of the polyethylene powder that is not in contact with the plasticizer deteriorates, and as a result, there is a tendency to remain in the form of an unmelted material. In particular, when the molecular weight of the polyethylene powder is high, this tendency becomes stronger.

[0093] On the other hand, the polyethylene powder of the present embodiment can suppress unmelted matter because the plasticizer is impregnated quickly and has good dispersibility.

[0094] In addition, the entangled state of the molecular chain formed when the polyethylene powder is usually extruded in a plasticizer is related to the entangled state of the molecular chain in the microporous membrane obtained by stretching after the extrusion process. Therefore, when the entangled state of the molecular chain formed during the extrusion process is uneven, a strong entanglement site of the molecular chain and a weak entanglement site of the molecular chain are generated in the microporous membrane. The site where the molecular chain in the microporous membrane is entangled strongly is easy to shrink so that the hole becomes smaller, and the hole becomes larger around it. Since the amount of ion permeation becomes more in the site where the hole becomes larger, when the microporous membrane is used as a battery separator, there is a tendency to easily deteriorate and short-circuit during repeated charge and discharge. In addition, when the entanglement of the molecular chain is too strong, there is a tendency for the fluidity at the shutdown temperature to deteriorate.

[0095] On the other hand, the polyethylene powder of the present embodiment forms a uniform and appropriate entangled state of molecular chains by extrusion processing, so the microporous membrane obtained after the extrusion processing has a uniform pore structure, and the pores are easily blocked during shutdown.

[0096] In order to make the slope of the straight line connecting the two maximum points in the torque curve obtained when the polyethylene powder is kneaded under the above <kneading conditions> show a value within the above specified range, the polyethylene powder needs to have a pore structure that is easy to impregnate the plasticizer and the entanglement state of the molecular chains in the polyethylene powder can be easily uniformed during the kneading process. In addition, as the characteristics of the polyethylene powder that meet these requirements, for example, the pores on the surface of the polyethylene powder become larger and the molecular chains on the surface of the polyethylene powder are less entangled.

[0097] As methods for controlling the slope of the straight line connecting the two maximum points in the torque curve obtained when the polyethylene powder is kneaded under the above <kneading conditions> within the above numerical range, there can be listed: reducing the entanglement of the molecular chains on the surface of the polyethylene powder, and expanding the pores on the surface of the polyethylene powder by accelerating the growth reaction of the molecular chains in the second half of the polymerization. Specifically, there can be listed: satisfying the following <Formula (I)> in the multi-step polymerization process described later; copolymerizing the comonomers in a flash tank located between the reactors in the multi-step polymerization process described later; introducing the comonomers into the flash tank located after the reactor, and then polymerizing to form a low-density ethylene copolymer, etc.

[0098] <Formula (I)>

[0099] (Last stage reactor temperature)-(First stage reactor temperature)≥20℃

[0100] When the polyethylene powder is obtained by polymerization, the active site of the polymerization reaction is present in the center of the polyethylene powder, so it is presumed that the polyethylene generated in the first half of the polymerization process is present on the surface side of the polyethylene powder, and the polyethylene generated in the second half of the polymerization process is present on the center side of the polyethylene powder. Therefore, by performing the polymerization at a low temperature in the first half of the polymerization process, molecular chains with less entanglement can be generated on the surface of the polyethylene powder, so that in the early stage of the kneading process, the molecular chains on the surface of the polyethylene powder are quickly dispersed, and there is a tendency to easily disperse the entanglement of the molecular chains in the center.

[0101] In addition, in the second half of the polymerization process, the surface of the polyethylene powder is easily stretched under the pressure of the molecular chains generated in the center of the polyethylene powder, thereby disentangling and enlarging the pores. In addition, by performing polymerization at a high temperature in the second half of the polymerization process, the effect of disentangling the molecular chains on the surface of the polyethylene powder and the effect of enlarging the pores are further increased. Moreover, by forming a low-density ethylene copolymer by post-polymerization after the polymerization process, the polyethylene powder of this embodiment is made into a mixture of multiple polymers, which can further improve these effects.

[0102] The measurement of the torque curve based on the above-mentioned <kneading conditions> in order to define the physical properties of the polyethylene powder according to the present embodiment is specifically performed by the following method.

[0103] First, 24 g of liquid paraffin was added to a laboratory mixing extruder mixer (main body model: 30C150, mixer model: R-60) manufactured by Toyo Seiki Co., Ltd., which was set at a temperature of 114°C, and mixed for 10 minutes at a rotation speed of 5 rpm. 16 g of the polyethylene powder of the present embodiment and 0.4 g of an antioxidant were added to the liquid paraffin, the rotation speed was adjusted to 30 rpm and mixed for 3 minutes, and then mixed while raising the set temperature from 114°C to 163°C in 1 minute without changing the rotation speed. After the temperature was raised, mixing was performed for 5 minutes at a set temperature of 163°C and a rotation speed of 30 rpm. Next, the average torque (rotational load generated during mixing) [N·m] calculated using the laboratory mixing extruder mixer test program version 4.52 (copyright (C) Toyo Seiki Co., Ltd.) was used as the vertical axis, and the mixing time [minutes] was used as the horizontal axis, thereby obtaining a torque curve. At this time, the average torque value is plotted every approximately 0.125 seconds, and then the elapsed time and torque value when the maximum value is reached are read.

[0104] In the above <kneading conditions>, the polyethylene powder and the antioxidant are preferably mixed in advance in a resin container.

[0105] The liquid paraffin used under the above <kneading conditions> may be any liquid paraffin that functions as a plasticizer and forms a uniform solution at a temperature not lower than the melting point of the polyethylene powder when kneaded with the polyethylene powder.

[0106] Liquid paraffin refers to the purest hydrocarbon compound (oil) obtained by removing impurities such as aromatic hydrocarbons and sulfur compounds contained in the lubricating oil fraction of petroleum using sulfuric anhydride and fuming sulfuric acid, and purifying to a high purity. In addition, liquid paraffin is colorless, transparent, tasteless and odorless, and examples thereof include white oil (light oil), mineral oil, etc.

[0107] As the antioxidant used in the above-mentioned <Mixing Conditions>, a phenolic antioxidant is preferably used as a primary antioxidant, and there are no particular restrictions. Examples thereof include 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0108] The torque curve obtained when kneading is performed under the above <kneading conditions> includes a first peak obtained by the plasticizer impregnating and swelling the polyethylene powder and a second peak obtained by the polyethylene powder dissolving and dispersing in the plasticizer.

[0109] Furthermore, the time from the observation of the maximum point A in the first peak to the observation of the maximum point B in the second peak corresponds to the time required from the plasticizer infiltrating into the polyethylene powder to the polyethylene powder being dispersed in the plasticizer, and the easier the plasticizer is to infiltrate, the shorter this time is. In addition, the difference in the rotation load generated during kneading, which is the value of the vertical axis of the first maximum point A and the second maximum point B, corresponds to the change in viscosity of the system before and after the dispersion of the polyethylene powder, and the better the dispersibility of the polyethylene powder is and the stronger the entanglement of the molecular chains formed during the kneading process, the greater this change is.

[0110] More specifically, the slope of a straight line connecting two maximum points in the torque curve of the present embodiment can be measured by a method described in Examples to be described later.

[0111] (Mixing energy during swelling in torque curve (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ))

[0112] In the torque curve obtained when the polyethylene powder of the present embodiment is kneaded under the above <kneading conditions>, the kneading energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / EB ) is preferably 0.02 to 0.3, more preferably 0.02 to 0.2, and further preferably 0.02 to 0.1.

[0113] The kneading energy (E) during swelling in the torque curve obtained when the polyethylene powder of the present embodiment is kneaded under the above <kneading conditions> is A ) is the integral value of the torque per unit volume from the point at which the temperature starts to rise to the minimum point between the first peak and the second peak. The greater the amount of plasticizer infiltrated into the polyethylene powder, the greater the value.

[0114] The kneading energy (E B ) is the integral value of the torque per unit volume from the minimum point between the first peak and the second peak to the end of kneading. The stronger the entanglement of the molecular chains formed during the kneading process, the higher the value.

[0115] The kneading energy during the above swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is 0.02 or more, and the plasticizer is infiltrated into the polyethylene powder in an appropriate amount during swelling, further suppressing the generation of unmelted matter. In addition, there is a tendency that the fluidity of the polyethylene resin during melting is better. Therefore, there is a tendency that a microporous membrane with a more excellent appearance and a further improved shutdown function can be manufactured.

[0116] On the other hand, by the above ratio (E A / E B ) is below 0.3, there is a tendency to suppress the necessary amount of plasticizer. In addition, there is a tendency that the entanglement of the molecular chains formed during the mixing process becomes uniform. Therefore, there is a tendency to reduce the production cost and environmental load in the manufacture of the microporous membrane, and to manufacture a microporous membrane with a more uniform pore structure.

[0117] Specifically, the kneading energy (E) during swelling in the torque curve obtained when the polyethylene powder of the present embodiment is kneaded under the above-mentioned <kneading conditions> is A ) and the mixing energy during melting (E B ) ratio (E A / E B ) can be measured by the method described in the examples.

[0118] The above ratio (E A / E B) can be controlled within the above numerical range by adjusting the molecular weight and density of the polyethylene produced in the first half of the polymerization process and the molecular weight and density of the polyethylene produced in the second half of the polymerization process or in a process after the polymerization.

[0119] (Mixing energy at the beginning of swelling (E 0 ))

[0120] In the torque curve obtained when the polyethylene powder of the present embodiment is kneaded under the above <kneading conditions>, the kneading energy (E 0 ) is preferably the total mixing energy (E t ) is less than 5%, more preferably the total kneading energy (E t ) is less than 1%, and more preferably the total kneading energy (E t ) is less than 0.1%.

[0121] In addition, the lower limit is not particularly limited, but is usually 0% or more.

[0122] The kneading energy (E 0 ) is the integral value of the torque per unit volume of the polyethylene powder from the start of kneading to the start of temperature rise. When a low melting point polyethylene component that starts to melt before swelling exists on the powder surface, this value takes a value greater than 0.

[0123] The kneading energy (E 0 ) is the total mixing energy (E t ) is less than 5%, the generation of unmelted matter can be suppressed, and there is a tendency that a microporous membrane with a better appearance can be produced.

[0124] As the kneading energy (E 0 ) method, for example, there can be mentioned a method of adjusting the amount of the comonomer in the first half of the polymerization step, etc.

[0125] Specifically, the kneading energy (E) at the start of swelling in this embodiment is 0 ) can be measured by the method described in the examples described later.

[0126] (Median particle size)

[0127] The median particle size of the polyethylene powder of the present embodiment is preferably in the range of 50 μm or more and 250 μm or less, more preferably 60 μm or more and 200 μm or less, and even more preferably 70 μm or more and 150 μm or less.

[0128] The median particle size of the polyethylene powder of the present embodiment is a particle size (D50) when the cumulative mass reaches 50%.

[0129] When the median particle size is 50 μm or more, the ease of handling of the polyethylene powder in the production process and the extrusion processing process (improvement of fluidity, suppression of dust, etc.) is improved.

[0130] On the other hand, when the median particle size is 250 μm or less, the plasticizer can easily penetrate into the center of the polyethylene powder, and the generation of unmelted matter can be suppressed.

[0131] Examples of methods for controlling the median particle size of the polyethylene powder of this embodiment within the above numerical range include: a method of controlling the particle size of the polymerization catalyst; a method of adjusting the polymerization conditions described below so as to suppress rapid polymerization reaction (hereinafter sometimes referred to as rapid polymerization); and the like.

[0132] Specifically, the median particle size of the polyethylene powder according to the present embodiment can be measured by the method described in Examples described later.

[0133] (density)

[0134] The density of the polyethylene powder of this embodiment is preferably in the range of 920 kg / m 3 Above and 960kg / m 3 Below, more preferably 930kg / m 3 Above and 955kg / m 3 Below, more preferably 935kg / m 3 Above and 950kg / m 3 the following.

[0135] The density of the polyethylene powder of this embodiment is 920 kg / m 3 Above and 960kg / m 3 Next, the microporous membrane using the polyethylene powder of the present embodiment has an excellent balance between dimensional stability and mechanical strength.

[0136] Examples of methods for controlling the density of the polyethylene powder of the present embodiment within the above numerical range include a method of adjusting the amount of comonomers other than ethylene in the polymerization step and a method of adjusting the molecular weight of the polymer.

[0137] Specifically, the density of the polyethylene powder according to the present embodiment can be measured by the method described in Examples described later.

[0138] [Method for producing polyethylene powder]

[0139] Hereinafter, the method for producing the polyethylene powder according to the present embodiment will be described.

[0140] (Catalyst component)

[0141] The polyethylene powder of the present embodiment can be produced by polymerizing ethylene or polymerizing ethylene and other comonomers using a predetermined catalyst component.

[0142] The catalyst component used for producing the ethylene-based polymer constituting the polyethylene powder of the present embodiment is not particularly limited, and examples thereof include a Ziegler-Natta catalyst and a metallocene catalyst.

[0143] Examples of methods for producing Ziegler-Natta catalysts and metallocene catalysts include methods described in Japanese Patent No. 5782558 and Japanese Unexamined Patent Application Publication No. 2019-19265.

[0144] (Method for producing ethylene polymer)

[0145] Examples of a method for polymerizing the ethylene-based polymer constituting the polyethylene powder of the present embodiment include a method of polymerizing ethylene by a suspension polymerization method or a gas phase polymerization method, or a method of copolymerizing ethylene and a comonomer.

[0146] Among them, the suspension polymerization method is preferred because it can effectively remove the heat of polymerization.

[0147] In the suspension polymerization method, an inert hydrocarbon solvent can be used as a solvent, and olefin itself can also be used as a solvent.

[0148] There are no particular restrictions on the inert hydrocarbon solvent, and examples thereof include: aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, and dichloromethane; and mixtures thereof.

[0149] The polymerization temperature in the polymerization step of the ethylene-based polymer is preferably 40°C to 100°C, more preferably 45°C to 95°C, and even more preferably 50°C to 90°C.

[0150] When the polymerization temperature is 40° C. or higher, efficient production can be achieved industrially. On the other hand, when the polymerization temperature is 100° C. or lower, the generation of bulk scale due to partial melting of the polymer can be suppressed, and the ethylene polymer can be produced continuously and stably without clogging the pipeline.

[0151] The polymerization pressure in the polymerization step of the ethylene-based polymer is preferably normal pressure or higher and 2 MPaG or lower, more preferably 0.2 MPaG or higher and 1.5 MPaG or lower, and still more preferably 0.3 MPaG or higher and 0.9 MPaG or lower.

[0152] When the polymerization pressure is equal to or higher than normal pressure, the production can be performed efficiently on an industrial scale.

[0153] On the other hand, when the polymerization pressure is 2 MPaG or less, the generation of bulk scale due to rapid polymerization in the polymerization reactor can be prevented, and there is a tendency that an ethylene-based polymer can be stably produced.

[0154] Generally, when obtaining an ethylene polymer by polymerization, an antistatic agent such as Stadis manufactured by Innospec (agent: Maruwa Bussan Co., Ltd.) or STATSAFE manufactured by Innospec is preferably used to suppress static adhesion of the ethylene polymer to the polymerization reactor.

[0155] The antistatic agent such as Stadis and STATSAFE may be added to the solid catalyst in advance, or may be added to the polymerization reactor by diluting it in an inert hydrocarbon solvent using a pump or the like.

[0156] In either the method of pre-adding to the solid catalyst or the method of adding to the polymerization reactor, the amount of the antistatic agent added is preferably 1 ppm or more and 500 ppm or less, more preferably 10 ppm or more and 100 ppm or less, relative to the production of the ethylene polymer per unit time.

[0157] As described in the specification of German Patent Application Publication No. 3127133, the molecular weight of ethylene polymers can be controlled by allowing hydrogen to exist in the polymerization system or changing the polymerization temperature, etc. By adding hydrogen as a chain transfer agent in the polymerization system, the molecular weight of the ethylene polymer can be controlled within an appropriate range.

[0158] When the molecular weight of the ethylene polymer is controlled by adding hydrogen to the polymerization system, the mole fraction of hydrogen is preferably in the range of 0 mol % to 50 mol %, more preferably 0 mol % to 30 mol %.

[0159] In addition, when adding hydrogen in the polymerization system, hydrogen can also be added to the polymerization system from the catalyst introduction line after being contacted with the catalyst in advance. After the catalyst is just introduced into the polymerization system, the catalyst concentration near the introduction line outlet becomes high, so rapid polymerization is carried out, and the possibility of producing a local high temperature state is improved. On the other hand, by contacting hydrogen and the catalyst before being introduced into the polymerization system, the initial activity of the catalyst can be suppressed, and the generation of block fouling caused by rapid polymerization, the deactivation of the catalyst under high temperature, etc. can be suppressed.

[0160] The polymerization reaction can be carried out in any of a batch method, a semi-continuous method and a continuous method, but is preferably carried out in a continuous method.

[0161] By continuously supplying ethylene gas, solvent, catalyst, etc. into the polymerization system and continuously discharging them together with the produced ethylene polymer, it is possible to suppress a local high temperature state due to a rapid ethylene reaction, and the polymerization system can be made more stable.

[0162] When ethylene reacts in a uniform state in the polymerization system, it is possible to suppress the generation of branches, double bonds, etc. in the polymer chain, or to suppress the generation of low molecular weight components and ultra-high molecular weight bodies due to the decomposition and cross-linking of ethylene polymers, and to easily generate crystalline components of ethylene polymers. Thus, it is easy to obtain the necessary amount of crystalline components sufficient to achieve the strength required for membranes, microporous membranes, etc.

[0163] In addition, the polymerization reaction of ethylene polymers can be a single-step polymerization method using one polymerization reactor, or a multi-step polymerization method in which polymerization is carried out sequentially and continuously in two or more polymerization reactors connected in series. However, from the perspective of being able to effectively control the structure of the surface and center parts of the polyethylene powder, it is preferred to use a multi-step polymerization method.

[0164] Specifically, the production of the ethylene-based polymer using the multi-step polymerization method is carried out by the method shown below.

[0165] First, an ethylene-based polymer X is produced in a first-stage polymerization reactor under the above-mentioned production conditions, and the ethylene-based polymer X extracted from the first-stage polymerization reactor is transferred to an intermediate flash tank to separate unreacted ethylene, hydrogen, and comonomers in the case of copolymerization in the first-stage polymerization reactor.

[0166] Next, the suspension containing the ethylene-based polymer X is transferred to a second-stage polymerization reactor, and the ethylene-based polymer Y is produced under the above-mentioned production conditions.

[0167] The difference between the temperature of the first stage polymerization reactor and the temperature of the second stage polymerization reactor preferably satisfies the following <Formula 1>, more preferably satisfies the following <Formula 2>, and further preferably satisfies the following <Formula 3>.

[0168] It should be noted that the second level is the final level.

[0169] <Formula 1>

[0170] (Second stage reactor temperature)-(First stage reactor temperature)≥20℃

[0171] <Formula 2>

[0172] (Second stage reactor temperature)-(First stage reactor temperature)≥25℃

[0173] <Formula 3>

[0174] (Second stage reactor temperature)-(First stage reactor temperature)≥30℃

[0175] The lower the polymerization temperature, the more the movement of the growing ethylene polymer molecular chains is suppressed, and the less entanglement of the generated molecular chains is. Therefore, by performing low-temperature polymerization in the first-stage polymerization reactor, molecular chains with less entanglement can be generated on the surface of the polyethylene powder, so that the surface of the polyethylene powder is easily stretched under the pressure from the molecular chains of the ethylene polymer generated in the second-stage polymerization reactor.

[0176] In addition, by performing high-temperature polymerization in the second-stage polymerization reactor, the mobility of the molecular chains on the surface of the polyethylene powder is improved, and the pressure from the molecular chains growing inside the polyethylene powder is increased. Therefore, by satisfying the above-mentioned <Formula 1> to <Formula 3>, the entanglement of the molecular chains on the surface of the polyethylene powder is small, the molecular chains are easily dispersed during the kneading process, and the pores are fully expanded, which can further improve the impregnation of the plasticizer.

[0177] The pressure of the intermediate flash tank is preferably 0.01 MPaG or more and 0.2 MPaG or less from the viewpoint of accurately controlling the physical properties of the ethylene-based polymer Y. In addition, from the viewpoint of stretching the surface of the polyethylene powder containing the ethylene-based polymer X produced in the first-stage polymerization reactor and improving the efficiency of introducing the ethylene monomer into the center of the polyethylene powder in the second-stage polymerization reactor, the temperature of the intermediate flash tank is preferably 70° C. or more and 100° C. or less, and it is further preferred to supply the comonomer to the flash tank.

[0178] The proportion of ethylene polymer Y contained in the polyethylene powder produced by the above-mentioned multi-step polymerization method, that is, the range of the production of ethylene polymer in the second-stage polymerization reactor, that is, the content is preferably 30% to 70%, more preferably 35% to 65%, and further preferably 40% to 65%.

[0179] When the content of the ethylene-based polymer Y is 30% or more, the pores on the surface of the polyethylene powder can be enlarged, and the permeability of the plasticizer can be further improved.

[0180] On the other hand, as the content of ethylene polymer Y increases, it is necessary to reduce the activity and shorten the residence time in the first stage polymerization reactor, or to increase the activity and extend the residence time in the second stage polymerization reactor. Therefore, by setting the content of ethylene polymer Y to 70% or less, stable production can be performed without subjecting the temperature and pressure of each polymerization reactor to extreme conditions.

[0181] The ethylene polymer X obtained in the first stage polymerization reactor has a preferred density range of 930 kg / m from the viewpoint of preventing pore clogging before swelling during extrusion processing. 3Above and 960kg / m 3 Below, more preferably 935kg / m 3 Above and 960kg / m 3 Below, more preferably 940kg / m 3 Above and 960kg / m 3 the following.

[0182] The viscosity average molecular weight of the ethylene-based polymer X is not particularly limited as long as the viscosity average molecular weight of the polyethylene powder finally produced is within the above range.

[0183] The preferred range of density of the ethylene polymer Y obtained in the second stage polymerization reactor is 920 kg / m from the viewpoint of enlarging the pores on the surface of the polyethylene powder and reducing the amount of plasticizer required during molding. 3 Above and 950kg / m 3 Below, more preferably 920kg / m 3 Above and 945kg / m 3 the following.

[0184] In addition, there is no particular limitation on the range of the viscosity average molecular weight of the ethylene-based polymer Y as long as the viscosity average molecular weight of the polyethylene powder finally produced is within the above range, but from the viewpoint of reducing the necessary amount of plasticizer during molding, it is preferably 10,000 to 2,000,000, and more preferably 10,000 to 1,500,000.

[0185] The above-mentioned viscosity average molecular weight and density, which are physical properties of the ethylene polymer Y, can be determined based on the addition property according to the production amounts in each polymerization reactor by measuring the physical properties of the ethylene polymer X extracted from the first polymerization reactor and the finally produced polyethylene powder.

[0186] A suspension of ethylene-based polymers constituting the polyethylene powder of the present embodiment is quantitatively extracted from the polymerization reactor and transported to a final flash tank to separate unreacted ethylene, hydrogen, and other comonomers in the case of copolymerization in the polymerization reactor. The final flash tank is preferably at a pressure of 0.05 MPaG to 0.5 MPaG and a temperature of 70° C. to 100° C. from the viewpoint of stretching the surface of the polyethylene powder obtained in the polymerization reactor, and it is further preferred to supply other comonomers.

[0187] In the method for producing the ethylene polymer constituting the polyethylene powder of the present embodiment, solvent separation is performed after the polymerization step. The solvent separation method can be decantation, centrifugal separation, filter filtration, etc., and centrifugal separation with high separation efficiency of the ethylene polymer and the solvent is more preferred.

[0188] The solvent content of the ethylene polymer after solvent separation is not particularly limited, but is preferably 20% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 60% by mass or less, relative to the mass of the ethylene polymer.

[0189] When the solvent content is 20% by mass or more, post-polymerization proceeds in the center of the polyethylene powder, and the surface of the polyethylene powder tends to be stretched.

[0190] On the other hand, when the solvent content is 70% by mass or less, low molecular weight components contained in the solvent, namely wax, are less likely to remain in the polyethylene powder, and a decrease in the heat resistance of the microporous membrane due to the inclusion of wax can be suppressed.

[0191] In the method for producing the ethylene polymer constituting the polyethylene powder of the present embodiment, the catalyst used in the polymerization step is deactivated after the polymerization step. The catalyst deactivation is not particularly limited, but is preferably performed after the ethylene polymer is separated from the solvent.

[0192] By introducing a reagent for deactivating the catalyst after separation from the solvent, it is possible to suppress precipitation of low molecular weight components, catalyst components, etc. contained in the solvent into the ethylene-based polymer.

[0193] Examples of the agent for deactivating the catalyst include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, and alkynes.

[0194] In the method for producing the ethylene-based polymer constituting the polyethylene powder of the present embodiment, a drying step is performed after the solvent separation.

[0195] In the drying step, a rotary kiln method, a paddle method, a fluidized bed drying method or the like is preferably used.

[0196] The drying temperature is preferably 50° C. or higher and 150° C. or lower, and more preferably 70° C. or higher and 110° C. or lower.

[0197] In addition, it is also effective to introduce an inert gas such as nitrogen into the dryer to promote drying. In this case, a method of adding steam or the like as a reagent for deactivating the catalyst is also more effective.

[0198] After the ethylene-based polymer constituting the polyethylene powder of the present embodiment is dried, it may be sieved to remove coarse powder.

[0199] The polyethylene powder of the present embodiment may be a mixture of a plurality of polyethylene powders containing an ethylene-based polymer obtained by the above-mentioned production method.

[0200] Furthermore, the polyethylene powder of the present embodiment may be used in combination with known additives such as a slip agent, a neutralizer, an antioxidant, a light stabilizer, an antistatic agent, and a pigment, as necessary.

[0201] The lubricant or neutralizer is not particularly limited, and examples thereof include aliphatic hydrocarbons, higher fatty acids, higher fatty acid metal salts, fatty acid esters of alcohols, waxes, higher fatty acid amides, silicone oils, rosin, etc. Specifically, stearates such as calcium stearate, magnesium stearate, and zinc stearate can be cited as appropriate additives.

[0202] The antioxidant is not particularly limited, but for example, phenolic compounds, phenolic phosphorus-containing compounds, and phosphorus-containing compounds are preferred. Specifically, examples include: phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol (butylhydroxytoluene), octadecyl 3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate, and tetrakis(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane; phenolic phosphorus-containing antioxidants such as 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphophetidine; and phosphorus-containing antioxidants such as 4,4'-biphenylene diphosphite tetrakis(2,4-di-tert-butylphenyl) ester, tris(2,4-di-tert-butylphenyl) phosphite, and cyclic neopentanetetraylbis(2,4-tert-butylphenyl phosphite).

[0203] The light stabilizer is not particularly limited, and examples thereof include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based light stabilizers such as di(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino)hexamethylene}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}].

[0204] The antistatic agent is not particularly limited, and examples thereof include aluminosilicate, kaolin, clay, natural silica, synthetic silica, silicates, talc, diatomaceous earth, and fatty acid glycerides.

[0205] [use]

[0206] The polyethylene powder of this embodiment can be used as a raw material for various molded bodies such as microporous membranes, high-strength fibers, sintered bodies, press-molded bodies, and plunger extrusion-molded bodies, and is particularly suitable as a raw material for microporous membranes for battery separators.

[0207] [Molding body]

[0208] The molded product of the present embodiment is a molded product obtained by molding the polyethylene powder of the present embodiment described above.

[0209] The molded body of the present embodiment can be obtained by, for example, introducing the polyethylene powder of the present embodiment into an extruder, molding it into a desired shape such as a sheet, and performing a drying treatment.

[0210] Examples of the molded product of the present embodiment include microporous films, and more specifically, battery separators, and more specifically, lithium ion secondary battery separators, lead acid battery separators, and the like.

[0211] As a method for producing a microporous membrane, there can be mentioned a molding method which involves the steps of extrusion of a resin using a wet extrusion method, stretching, extraction, and drying.

[0212] Example

[0213] Hereinafter, the present embodiment will be described in more detail by using specific examples and comparative examples, but the present embodiment is not limited to the following examples and comparative examples.

[0214] The measurement methods of various characteristics and properties are shown below.

[0215] [Physical properties of polyethylene powder]

[0216] The method for evaluating the physical properties of the polyethylene powder will be described.

[0217] (Viscosity average molecular weight (Mv))

[0218] The viscosity average molecular weight of the polyethylene powder is measured by the method shown below in accordance with ISO 1628-3 (2010).

[0219] First, weigh polyethylene powder in the range of 4.0 mg to 4.5 mg in a dissolving tube. The weighed mass is recorded as "m (unit: mg)" in the following formula. Use a vacuum pump to exhaust the air inside the dissolving tube and replace it with nitrogen. Then, add 20 mL of decalin (added with 1 g / L of 2,6-di-tert-butyl-4-methylphenol, hereinafter referred to as decalin) that has been degassed with a vacuum pump and replaced with nitrogen. Stir at 150°C for 90 minutes to dissolve the polyethylene powder, thereby preparing a decalin solution.

[0220] Then, the decalin solution was placed in a Cannon-Fenske viscometer (manufactured by Shibata Scientific Instruments Co., Ltd. / viscometer No. 100) in a constant temperature liquid bath at 135° C., and the falling time (ts) between the marked lines was measured.

[0221] In addition, the falling time (tb) of decalin alone without adding polyethylene powder was measured as a blank, and the specific viscosity (ηsp) was calculated according to the following (Formula A).

[0222] ηsp=(ts / tb)-1(Formula A)

[0223] The intrinsic viscosity IV was calculated from the specific viscosity (ηsp) and the concentration (C) (unit: g / dL) using the following (Formula B) and (Formula C).

[0224] Concentration C = m / (20×γ) / 10 (unit: g / dL) (Formula B)

[0225] γ = (density of decalin at 20°C (in g / mL)) / (density of decalin at 135°C (in g / mL))

[0226] =0.888 / 0.802=1.107

[0227] Intrinsic viscosity IV = (ηsp / C) / (1+0.27×ηsp) (Formula C)

[0228] The intrinsic viscosity IV is substituted into the following (Formula D) to determine the viscosity average molecular weight (Mv).

[0229] Viscosity average molecular weight (Mv) = (5.34 × 10 4 )×[η] 1.49 (Formula D)

[0230] (The slope of the straight line connecting two maximum points in the torque curve)

[0231] The slope of a straight line connecting two maximum points in a torque curve obtained during kneading is determined by the method shown below.

[0232] First, 24 g of liquid paraffin (product name: P-350P) manufactured by MORESCO was added to a laboratory mixing extruder mixer (main body model: 30C150, mixer model: R-60) manufactured by Toyo Seiki Co., Ltd. set at a temperature of 114°C, and mixed for 10 minutes at a rotation speed of 5 rpm.

[0233] To the liquid paraffin was added a mixture of 16 g of polyethylene powder and 0.4 g of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20) manufactured by Ooko Chemical Japan Co., Ltd., which had been thoroughly mixed in advance in a resin container, and kneaded for 3 minutes at a rotation speed of 30 rpm.

[0234] Then, kneading was performed while the set temperature was raised from 114° C. to 163° C. over 1 minute without changing the rotation speed. After the temperature was raised, kneading was performed for 5 minutes under the conditions of the set temperature of 163° C. and the rotation speed of 30 rpm.

[0235] Next, the average torque (rotational load generated during kneading) calculated using the Laboratory Kneading Extruder Mixer Test Program Version 4.52 (Copyright (C) Toyo Seiki Co., Ltd.) was plotted on the vertical axis and the kneading time was plotted on the horizontal axis to obtain a torque curve. At this time, the average torque value was plotted every approximately 0.125 seconds.

[0236] Then, for the first maximum point A and the second maximum point B in the torque curve, the kneading elapsed time (t A ,t B ) and torque value (P A ,P B ), and find the slope of the straight line connecting the two maximum points (N·m / min) according to the following formula.

[0237] (Slope of the straight line) = (P B -P A ) / (t B -t A )

[0238] (Mixing energy during swelling in torque curve (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ))

[0239] The mixing energy (E) during swelling in the torque curve A ) and the mixing energy during melting (E B ) is calculated by the method shown below.

[0240] In the torque curve obtained by determining the slope of the straight line connecting the two maximum points in the torque curve, the integral value of the torque per unit volume from the point where the temperature starts to rise to the minimum point between the first peak and the second peak is calculated, and this value is taken as the kneading energy during swelling (E A ).

[0241] Furthermore, the integral value of the torque per unit volume from the minimum point between the first peak and the second peak to the kneading end point was calculated, and this value was taken as the kneading energy during melting (E B ).

[0242] Find E A With E B The ratio (E A / EB ).

[0243] (Mixing energy at the beginning of swelling (E 0 ) in the total mixing energy (E t )

[0244] The kneading energy (E) at the start of swelling was calculated by the following method: 0 ).

[0245] In the torque curve obtained by determining the slope of the straight line connecting the two maximum points in the torque curve, the integral value of the torque per unit volume from the point at which the polyethylene powder was kneaded to the point at which the temperature was raised was calculated, and this value was taken as the kneading energy (E) at the start of swelling. 0 ).

[0246] Furthermore, the integral value of the torque per unit volume from the kneading start point to the kneading end point was calculated, and this value was taken as the total kneading energy (E t ).

[0247] The total mixing energy (E t ) at the beginning of swelling (E 0 ) ratio.

[0248] (E 0 The ratio (%)) = (E 0 / E t )×100

[0249] (Median particle size)

[0250] The median particle size of the polyethylene powder was determined by the method shown below.

[0251] The polyethylene powder was classified using a sieve according to the JIS Z8801 standard. The mass of the polyethylene powder recovered in each fraction was measured using sieves with mesh sizes of 425 μm, 300 μm, 212 μm, 150 μm, 106 μm, 75 μm and 53 μm. Then, the fraction (mass %) of each fraction relative to the total mass of the polyethylene powder before classification was calculated, and the cumulative ratio from the side with a smaller mesh size, i.e., the cumulative undersize ratio (mass %), was calculated. A cumulative undersize distribution graph, i.e., a particle size distribution cumulative curve (cumulative curve from small particles), was drawn with the mesh size value as the horizontal axis and the cumulative undersize ratio as the vertical axis, and the value of the horizontal axis when the cumulative undersize ratio was 50% (D50 (μm)) was taken as the median particle size.

[0252] (density)

[0253] The density of the polyethylene powder was determined by the following methods (1) to (7).

[0254] (1) Polyethylene powder is filled into a mold of 100 mm×100 mm×2 mm thick.

[0255] (2) Using a press set at 190°C, at 10 kg / cm 2 Preheat for 3 minutes at 15kg / cm 2 Press down for 2 minutes.

[0256] (3) Cool the mold to room temperature by cold pressing.

[0257] (4) Slices of 20 mm×20 mm×2 mm in thickness were cut out from the obtained pressed sheet.

[0258] (5) The cut sections were placed in a test tube and heated at 120° C. for 1 hour under a nitrogen atmosphere.

[0259] (6) After heating, the mixture was cooled at 20° C. for 1 hour to obtain a molded product sample for density measurement.

[0260] (7) The density of the molded product sample was measured according to JIS K7112:1999 (D method), and the obtained value was taken as the density of the polyethylene powder (kg / m 3 ).

[0261] [Production of microporous membrane and evaluation of its properties]

[0262] (Method for producing microporous membrane)

[0263] 1 part by mass of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to 45 parts by mass of the polyethylene powder of each of Examples and Comparative Examples, and dry-blended using a tumble mixer to obtain a powder mixture.

[0264] The obtained powder mixture was replaced with nitrogen and then fed into a twin-screw extruder through a feeder under a nitrogen atmosphere.

[0265] Then, 55 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., P-350P (product name)) are injected into the above-mentioned twin-screw extruder in a side-feed manner, kneaded at 160°C, extruded from a T-die set at the front end of the twin-screw extruder, and then immediately cooled and solidified using a casting roll cooled to 25°C, thereby forming a gel-like sheet with a thickness of 1200 μm.

[0266] The gel-like sheet was stretched to 7×7 times at 115° C. to 125° C. using a simultaneous biaxial stretching machine, and the stretched film was then immersed in methyl ethyl ketone for 30 minutes to extract and remove the liquid paraffin, followed by drying.

[0267] Then, heat setting was performed at 115° C. to 125° C. for 3 minutes to obtain a microporous membrane.

[0268] The stretching temperature and the heat-setting temperature are appropriately adjusted for each microporous membrane within a specified temperature range.

[0269] (Evaluation of the number of defects in microporous membrane)

[0270] The number of defects existing in 250 mm×250 mm of the microporous film obtained by the above (Process for Producing Microporous Film) was visually counted. When the microporous film was observed with transmitted light, impurities such as dust observed as black spots were removed.

[0271] Then, based on the obtained number, the number of defects was evaluated according to the following evaluation criteria.

[0272] <Evaluation Criteria>

[0273] ◎(Good): Less than 1

[0274] ○(Normal): 2 or more and less than 5

[0275] ×(bad): 5 or more

[0276] (Evaluation of Uniformity of Pore Structure of Microporous Membrane)

[0277] For the microporous membrane obtained by the above (microporous membrane manufacturing method), 8 pieces of 100 mm × 50 mm microporous membranes were punched out from 250 mm × 250 mm, and the air permeability resistance specified in JIS P-8117 was measured for each microporous membrane using an Oken air permeability tester (model: EGO1) manufactured by Asahi Seiko Co., Ltd.

[0278] The measurement was performed at three locations on one microporous membrane of 100 mm×50 mm.

[0279] Then, the standard deviation of the measured values ​​at 24 points was calculated, and the uniformity of the air permeability was evaluated according to the following evaluation criteria, which was used as the evaluation of the uniformity of the pore structure of the microporous membrane.

[0280] <Evaluation Criteria>

[0281] ◎(Good): Less than 10 seconds

[0282] ○(Normal): Greater than or equal to 10 seconds and less than 20 seconds

[0283] × (difference): more than 20 seconds

[0284] (Evaluation of shutdown temperature of microporous membrane)

[0285] The microporous membrane obtained by the above (Process for producing microporous membrane) was impregnated with an electrolyte solution, and a battery having a structure in which the microporous membrane was sandwiched between SUS plate electrodes was prepared. The AC resistance of the battery was measured while the temperature was raised.

[0286] Then, the temperature at which the resistance value suddenly increased was defined as the shutdown temperature, and evaluation was performed based on the following evaluation criteria.

[0287] <Evaluation Criteria>

[0288] ◎(Good): Less than 132℃

[0289] ○(Normal): 132℃ or higher and less than 134℃

[0290] × (poor): above 134℃

[0291] [Production Example 1]

[0292] (Preparation of Ziegler-Natta Catalyst (A))

[0293] The Ziegler-Natta catalyst (A) was prepared according to the following (1) to (4).

[0294] <(1) Synthesis of raw material (a-1)>

[0295] 1 mol / L Mg was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. 6 (C 4 H 9 ) 12 Al(C 2 H 5 ) 3 2,000 mL of hexane solution (equivalent to 2,000 mmol in total of magnesium and aluminum) was added to the autoclave, and 146 mL of 5.47 mol / L n-butanol hexane solution was added dropwise from the feed line connected to the autoclave over 3 hours while stirring at 50°C. After the reaction was completed, the line was cleaned with 300 mL of hexane. Then, stirring was continued at 50°C for 2 hours. After the reaction was completed, the substance cooled to room temperature was used as raw material (a-1). Raw material (a-1) is an organic magnesium compound with a magnesium concentration of 0.704 mol / L.

[0296] <(2) Synthesis of raw material (a-2)>

[0297] 1 mol / L Mg was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. 6 (C 4 H 9 ) 12 Al(C 2 H 5 ) 32,000 mL of a hexane solution of 1,000 mol (equivalent to 2,000 mmol in total of magnesium and aluminum) was added, and while stirring at 80°C, 240 mL of a hexane solution of 8.33 mol / L methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pressure fed, and stirring was continued at 80°C for 2 hours. After the reaction was completed, the substance cooled to room temperature was used as raw material (a-2). The raw material (a-2) had a total concentration of magnesium and aluminum of 0.786 mol / L.

[0298] <(3) Synthesis of carrier (a-3)>

[0299] 1,000 mL of a 1 mol / L hexane solution of hydroxytrichlorosilane was placed in an 8L stainless steel autoclave after sufficient nitrogen substitution, and 1340 mL of a hexane solution of an organic magnesium compound of the raw material (a-1) (equivalent to 943 mmol of magnesium) was added dropwise at 65°C for 3 hours, and the reaction was continued while stirring at 65°C for another hour. After the reaction was completed, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain a carrier (a-3). The carrier was analyzed, and the magnesium contained in 1 g of solid was 7.5 mmol.

[0300] <(4) Preparation of Ziegler-Natta Catalyst (A)>

[0301] In an 8L stainless steel autoclave fully purged with nitrogen, 1,970mL of a hexane slurry containing 110g of the carrier (a-3) was stirred at 10°C, and 103mL of a 1 mol / L hexane solution of titanium tetrachloride and 131mL of the above-mentioned raw material (a-2) were added simultaneously over 3 hours. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, the supernatant was removed, and the unreacted raw material components were removed by washing with hexane 4 times, thereby preparing a Ziegler-Natta catalyst (A).

[0302] (Preparation of Ziegler-Natta Catalyst (B))

[0303] 1,600 mL of hexane was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen.

[0304] 800 mL of a 1 mol / L hexane solution of titanium tetrachloride and 800 mL of the above-mentioned raw material (a-2) were added simultaneously over 5 hours at 10°C with stirring.

[0305] The reaction was continued for 1 hour at 10° C. After the reaction was completed, the supernatant was removed, and the unreacted raw material components were removed by washing with hexane four times, thereby preparing a Ziegler-Natta catalyst (B).

[0306] [Manufacturing of polyethylene powder and microporous membrane]

[0307] (Example 1)

[0308] As shown below, in the first stage reactor, the ethylene polymer (X A ), and polymerized in the second stage reactor to obtain an ethylene polymer (Y A ), thereby obtaining polyethylene powder (A).

[0309] The viscosity average molecular weight of polyethylene powder (A) is 270,000 and the density is 945 kg / m 3 , the median particle size is 89μm.

[0310] Table 1 shows the results of the various evaluations performed on the polyethylene powder (A) and the microporous membrane of the polyethylene powder (A) produced by the above-mentioned (Method for producing microporous membrane).

[0311] <(1) Ethylene polymer (X A ) >

[0312] Polymerization of an ethylene-based polymer was carried out using a 300 L vessel-type polymerization reactor equipped with a stirring blade having three backward blades and three baffles.

[0313] The flow rate of 40L / hour is supplied with normal hexane as solvent, and stirring speed is set to 230rpm. Use above-mentioned Ziegler-Natta catalyst (A) as polymerization catalyst, and supply in a mode that makes the production speed of ethylene polymer be 7.1kg / hour. In polymerization catalyst, the antistatic agent STATSAFE 3000 (90g / L) manufactured by Innospec company utilizing normal hexane dilution is added with the amount of 20 mass ppm with respect to the production speed of ethylene polymer.

[0314] Triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) were used as the co-catalyst component and supplied at 10 mmol / hour. Hydrogen was supplied at 23 mol% (molar ratio: hydrogen / (ethylene+hydrogen)). The polymerization temperature was set to 50°C, the polymerization pressure was set to 0.37 MPaG, and the average residence time was set to 3.3 hours.

[0315] The ethylene polymer (X) obtained in the above manner A ) has a viscosity average molecular weight of 680,000 and a density of 943 kg / m 3 The polymerization activity in the first-stage reactor was 20,600 g per 1 g of the catalyst.

[0316] The polymerization slurry in the polymerization reactor was introduced into an intermediate flash tank at a pressure of 0.13 MPaG and a temperature of 80° C. in such a manner that the liquid level in the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated. 15 mol % (molar ratio: (1-butene) / (ethylene+hydrogen+(1-butene)) of 1-butene was supplied to the intermediate flash tank, and the average residence time was set to 1.3 hours.

[0317] <(2) Ethylene polymer (Y A ) >

[0318] The ethylene polymer (X A ) was transferred from the intermediate flash tank to a 300L container-type polymerization reactor equipped with a stirring blade with three backward blades and three baffles, and then the ethylene polymer (Y A )’s aggregation.

[0319] The stirring speed was set to 196 rpm, and triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) as co-catalyst components were supplied at 10 mmol / hour. Hydrogen was supplied at 26 mol% (molar ratio: hydrogen / (ethylene+hydrogen+(1-butene))), and 1-butene as a comonomer was supplied at 5.2 mol% (molar ratio: (1-butene) / (ethylene+hydrogen+(1-butene))). The polymerization temperature was set to 83°C, the polymerization pressure was set to 0.58 MPaG so that the production rate was 12.7 kg / hour, and the average residence time was set to 0.75 hours. The ethylene polymer (Y A ) has a viscosity average molecular weight of 40,000 and a density of 946 kg / m 3 The polymerization activity in the second-stage reactor was 8,300 g per 1 g of the catalyst.

[0320] The polymerization slurry in the polymerization reactor was introduced into a final flash tank at a pressure of 0.05 MPaG and a temperature of 80° C. so that the liquid level in the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated. The average residence time in the final flash tank was set to 1 hour.

[0321] Next, the polymerization slurry is continuously fed from the flash tank into a centrifuge by a pump to separate the polymer and the solvent, and then the separated ethylene polymer is fed into a rotary kiln type dryer controlled at 85° C. and dried while blowing nitrogen, thereby obtaining polyethylene powder (A).

[0322] In addition, in this drying step, steam is sprayed onto the polyethylene powder to deactivate the catalyst and the co-catalyst.

[0323] (Example 2)

[0324] As shown below, in the first stage reactor, the ethylene polymer (X B ), and polymerized in the second stage reactor to obtain an ethylene polymer (Y B ), thereby obtaining polyethylene powder (B).

[0325] The viscosity average molecular weight of polyethylene powder (B) is 290,000 and the density is 942 kg / m 3 , the median particle size is 96μm.

[0326] Table 1 shows the results of the various evaluations performed on the polyethylene powder (B) and the microporous membrane of the polyethylene powder (B) produced by the above-mentioned (Method for producing microporous membrane).

[0327] <(3) Ethylene polymers (X B ) >

[0328] The same conditions as in Example 1 were used except that the production rate was set to 7.2 kg / hour, the supply amount of hydrogen was set to 16 mol%, the polymerization temperature was set to 57°C, and the polymerization pressure was set to 0.3 MPaG. A ) was polymerized in the same manner to obtain an ethylene polymer (X B The obtained ethylene polymer (X B ) has a viscosity average molecular weight of 690,000 and a density of 942 kg / m 3 The polymerization activity in the first-stage reactor was 30,000 g per 1 g of the catalyst.

[0329] The polymerization slurry in the polymerization reactor was introduced into a reactor in which the other conditions were set to the same as those in Example 1 except that the pressure was set to 0.1 MPaG. A ) in an intermediate flash tank under the same conditions.

[0330] <(4) Ethylene polymers (Y B ) >

[0331] The same method as in Example 1 was used except that the production rate was set to 11.8 kg / hour, the supply amount of hydrogen was set to 22 mol %, the polymerization temperature was set to 85° C., the polymerization pressure was set to 0.56 MPaG, and the supply amount of 1-butene was set to 7.4 mol %. A ) was polymerized in the same manner to obtain an ethylene polymer (Y B The obtained ethylene polymer (Y B ) has a viscosity average molecular weight of 45,000 and a density of 942 kg / m 3The polymerization activity in the second-stage reactor was 11,000 g per 1 g of the catalyst.

[0332] The polymerization slurry in the polymerization reactor was introduced into the reactor, and the other conditions were set to the same as those in Example 1 except that 15 mol % of 1-butene was supplied. A ) in a final flash tank under the same conditions as in Example 1, and then (Y A ) The same separation and drying operations were performed to obtain polyethylene powder (B).

[0333] (Example 3)

[0334] As shown below, in the first stage reactor, the ethylene polymer (X C ), and polymerized in the second stage reactor to obtain an ethylene polymer (Y C ), thereby obtaining polyethylene powder (C).

[0335] The viscosity average molecular weight of polyethylene powder (C) is 240,000 and the density is 944 kg / m 3 , the median particle size is 102μm.

[0336] Table 1 shows the results of the various evaluations performed on the polyethylene powder (C) and the microporous membrane of the polyethylene powder (C) produced by the above-mentioned (Method for producing microporous membrane).

[0337] <(5) Ethylene polymer (X C ) >

[0338] The production rate was set to 12.8 kg / hour, the supply amount of hydrogen was set to 44 mol%, the polymerization temperature was set to 78 mol, the polymerization pressure was set to 0.65 MPaG, the average residence time was set to 3 hours, and 5.7 mol% of 1-butene was supplied as a comonomer. A ) was polymerized in the same manner to obtain an ethylene polymer (X C The obtained ethylene polymer (X C ) has a viscosity average molecular weight of 60,000 and a density of 947 kg / m 3 The polymerization activity in the first-stage reactor was 57,000 g per 1 g of the catalyst.

[0339] The polymerization slurry in the polymerization reactor was introduced into the reactor, and the other conditions were set to the same as those in Example 1 except that the pressure was set to 0.2 MPaG. A ) in an intermediate flash tank under the same conditions.

[0340] <(6) Ethylene polymers (Y C ) >

[0341] The production rate was set to 7.2 kg / hour, the supply amount of hydrogen was set to 3 mol%, the polymerization temperature was set to 78°C, the polymerization pressure was set to 0.29 MPaG, the supply amount of 1-butene was set to 1.1 mol%, and the average residence time was set to 0.82 hours. A ) was polymerized in the same manner to obtain an ethylene polymer (Y C ).

[0342] The obtained ethylene polymer (Y C ) has a viscosity average molecular weight of 560,000 and a density of 939 kg / m 3 The polymerization activity in the second-stage reactor was 8,500 g per 1 g of the catalyst.

[0343] The polymerization slurry in the polymerization reactor is introduced into the (Y B ) in a final flash tank under the same conditions as in Example 1, and then (Y A ) The same separation and drying operations are performed to obtain polyethylene powder (C).

[0344] (Example 4)

[0345] <(7) Polymerization of polyethylene powder (D)>

[0346] Polymerization of polyethylene powder was carried out using a vessel-type 300 L polymerization reactor equipped with a stirring blade having three backward blades and three baffles.

[0347] n-Hexane was supplied as a solvent at a flow rate of 80 L / hour, and the stirring speed was set to 230 rpm. The above-mentioned Ziegler-Natta catalyst (A) was used as a polymerization catalyst, and was supplied so that the production rate of polyethylene powder was 9 kg / hour.

[0348] To the polymerization catalyst, an antistatic agent STATSAFE 3000 (90 g / L) manufactured by Innospec Corporation diluted with n-hexane was added in an amount of 20 ppm by mass relative to the production rate of the polyethylene powder.

[0349] Triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) were used as co-catalyst components and supplied at 10 mmol / hour. Hydrogen was supplied at 2.7 mol% (molar ratio: hydrogen / (ethylene+hydrogen)). The polymerization temperature was set to 78°C, the polymerization pressure was set to 0.3 MPaG, and the average residence time was set to 1.7 hours. The polymerization slurry in the polymerization reactor was introduced into a final flash tank at a pressure of 0.3 MPaG and a temperature of 80°C in such a manner that the liquid level in the polymerization reactor remained constant, and unreacted ethylene and hydrogen were separated. 15 mol% (molar ratio: (1-butene) / (ethylene+hydrogen+(1-butene))) of 1-butene was supplied to the final flash tank, and the average residence time of the final flash tank was set to 1 hour.

[0350] Next, the polymer slurry was continuously fed from the flash tank to a centrifuge by a pump to separate the polymer from the solvent, and the separated polyethylene powder was then fed to a rotary kiln type dryer controlled at 85° C. to be dried while blowing nitrogen.

[0351] In addition, in this drying step, steam is sprayed onto the polyethylene powder to deactivate the catalyst and the co-catalyst.

[0352] The polyethylene powder (D) obtained in the above manner had a viscosity average molecular weight of 700,000 and a density of 936 kg / m 3 , the median particle size was 108 μm. In addition, the polymerization activity in the reactor was 11,500 g per 1 g of the catalyst. The results of the above-mentioned various evaluations on the polyethylene powder (D) and the microporous membrane of the polyethylene powder (D) manufactured by the above-mentioned (method for manufacturing microporous membrane) are shown in Table 1.

[0353] (Example 5)

[0354] 50 parts by mass of the polyethylene powder (D) was added to 50 parts by mass of the polyethylene powder (E) obtained by polymerization as described below, and the mixture was dry-blended using a drum mixer to obtain a polyethylene powder (F).

[0355] The viscosity average molecular weight of polyethylene powder (F) is 500,000 and the density is 941 kg / m 3 , the median particle size is 99μm.

[0356] Table 1 shows the results of the various evaluations performed on the polyethylene powder (F) and the microporous membrane of the polyethylene powder (F) produced by the above-mentioned (Method for producing microporous membrane).

[0357] <(8) Polymerization of polyethylene powder (E)>

[0358] The polymerization was carried out under the same conditions as in Example 4 except that the amount of hydrogen added was set to 6 mol%. The viscosity average molecular weight of the obtained polyethylene powder (E) was 300,000 and the density was 945 kg / m 3 The median particle size was 90 μm. The polymerization activity in the reactor was 11,600 g per 1 g of the catalyst.

[0359] (Example 6)

[0360] As shown below, in the first stage reactor, the ethylene polymer (X G ), and polymerized in the second stage reactor to obtain an ethylene polymer (Y G ), thereby obtaining polyethylene powder (G).

[0361] The viscosity average molecular weight of polyethylene powder (G) is 900,000 and the density is 941 kg / m 3 , the median particle size is 90μm.

[0362] Table 1 shows the results of the various evaluations performed on the polyethylene powder (G) and the microporous membrane of the polyethylene powder (G) produced by the above-mentioned (Method for producing microporous membrane).

[0363] <(9) Ethylene polymers (X G ) >

[0364] The polymerization catalyst was set to Ziegler-Natta catalyst (B), the production rate was set to 6.9 kg / hour, the supply amount of hydrogen was set to 0.95 mol%, and the polymerization pressure was set to 0.3 MPaG. A ) was polymerized in the same manner to obtain an ethylene polymer (X G The obtained ethylene polymer (X G ) has a viscosity average molecular weight of 2,000,000 and a density of 937 kg / m 3 The polymerization activity in the first-stage reactor was 19,500 g per 1 g of the catalyst.

[0365] The polymerization slurry in the polymerization reactor was introduced into a reactor in which the other conditions were the same as those in Example 1 except that the pressure was set to 0.1 MPaG and 1-butene was not supplied. A ) in an intermediate flash tank under the same conditions.

[0366] <(10) Ethylene polymer (Y G ) >

[0367] The same method as in Example 1 was used except that the production rate was set to 12.9 kg / hour, the supply amount of hydrogen was set to 14.4 mol %, the polymerization temperature was set to 85°C, and the supply amount of 1-butene was set to 10.5 mol %. A ) was polymerized in the same manner to obtain an ethylene polymer (Y G ).

[0368] The obtained ethylene polymer (Y G ) has a viscosity average molecular weight of 300,000 and a density of 944 kg / m 3 The polymerization activity in the second-stage reactor was 33,000 g per 1 g of the catalyst.

[0369] The polymerization slurry in the polymerization reactor was introduced into a (Y A ) in a final flash tank under the same conditions as in Example 1, and then (Y A ) The same separation and drying operations were performed to obtain polyethylene powder (G).

[0370] (Example 7)

[0371] <(11) Polymerization of polyethylene powder (H)>

[0372] Polymerization was carried out under the same conditions as in Example 4 except that the polymerization catalyst was changed to the above-mentioned Ziegler-Natta catalyst (B), the production rate was changed to 10.0 kg / hour, and the amount of hydrogen added was changed to 0.56 mol %.

[0373] The obtained polyethylene powder (H) had a viscosity average molecular weight of 1,500,000 and a density of 930 kg / m 3 , the median particle size is 82μm.

[0374] The polymerization activity in the reactor was 59,500 g per 1 g of the catalyst.

[0375] Table 1 shows the results of the various evaluations performed on the polyethylene powder (H) and the microporous membrane of the polyethylene powder (H) produced by the above-mentioned (Method for producing microporous membrane).

[0376] (Comparative Example 1)

[0377] 64 parts by mass of the polyethylene powder (J) obtained by polymerizing as follows was added to 36 parts by mass of the polyethylene powder (I) obtained by polymerizing as follows, and dry-blended using a tumble mixer to obtain a polyethylene powder (K).

[0378] The viscosity average molecular weight of polyethylene powder (K) is 280,000 and the density is 946 kg / m3 , the median diameter is 76μm.

[0379] Table 1 shows the results of the various evaluations performed on the polyethylene powder (K) and the microporous membrane of the polyethylene powder (K) produced by the above-mentioned (Method for producing microporous membrane).

[0380] <(12) Polymerization of polyethylene powder (I)>

[0381] The polymerization was carried out under the same conditions as in Example 4, except that the flow rate of n-hexane was set to 40 L / hour, the production rate was set to 7.1 kg / hour, the amount of hydrogen added was set to 23 mol%, the polymerization temperature was set to 50°C, the polymerization pressure was set to 0.37 MPaG, the average residence time was set to 3.3 hours, the pressure of the final flash tank was set to 0.05 MPaG, and 1-butene was not supplied to the final flash tank.

[0382] The obtained polyethylene powder (I) had a viscosity average molecular weight of 680,000 and a density of 943 kg / m 3 The median particle size was 79 μm. The polymerization activity in the reactor was 20,600 g per 1 g of the catalyst.

[0383] <(13) Polymerization of polyethylene powder (J)>

[0384] The polymerization was carried out under the same conditions as in Example 4, except that the flow rate of n-hexane was set to 40 L / hour, the production rate was set to 12.8 kg / hour, the amount of hydrogen added was set to 44 mol %, the polymerization pressure was set to 0.65 MPaG, the average residence time was set to 3 hours, 5.7 mol % of 1-butene was supplied, the pressure of the final flash tank was set to 0.05 MPaG, and 1-butene was not supplied to the final flash tank.

[0385] The obtained polyethylene powder (J) had a viscosity average molecular weight of 60,000 and a density of 947 kg / m 3 , the median particle size is 75μm.

[0386] The polymerization activity in the reactor was 57,200 g per 1 g of the catalyst.

[0387] (Comparative Example 2)

[0388] As shown below, in the first stage reactor, the ethylene polymer (X L ), and polymerized in the second stage reactor to obtain an ethylene polymer (Y L ), thereby obtaining polyethylene powder (L).

[0389] The viscosity average molecular weight of polyethylene powder (L) is 280,000 and the density is 942 kg / m 3 , with a median diameter of 115 μm.

[0390] Table 1 shows the results of the various evaluations performed on the polyethylene powder (L) and the microporous membrane of the polyethylene powder (L) produced by the above-mentioned (Method for producing microporous membrane).

[0391] <(14) Ethylene polymers (X L ) >

[0392] The flow rate of n-hexane was set to 80 L / hour, the supply amount of hydrogen was set to 2.8 mol%, the polymerization temperature was set to 78°C, the polymerization pressure was set to 0.3 MPaG, the average residence time was set to 1.7 hours, 4.8 mol% of 1-butene was supplied, and the same conditions as in Example 1 (X A ) was polymerized in the same manner to obtain an ethylene polymer (X L The obtained ethylene polymer (X L ) has a viscosity average molecular weight of 710,000 and a density of 942 kg / m 3 The polymerization activity in the first-stage reactor was 20,900 g per 1 g of the catalyst.

[0393] The polymerization slurry in the polymerization reactor was introduced into a reactor in which the other conditions were set to the same as those in Example 1 except that the pressure was set to 0.1 MPaG. A ) in an intermediate flash tank under the same conditions.

[0394] <(15) Ethylene polymers (Y L ) >

[0395] The feed rate of hydrogen was set to 29 mol%, the polymerization temperature was set to 78° C., and the polymerization pressure was set to 0.65 MPaG. A ) was polymerized in the same manner to obtain an ethylene polymer (Y L The obtained ethylene polymer (Y L ) has a viscosity average molecular weight of 45,000 and a density of 942 kg / m 3 The polymerization activity in the second-stage reactor was 12,000 g per 1 g of the catalyst.

[0396] The polymerization slurry in the polymerization reactor was introduced into a (Y A ) in a final flash tank under the same conditions as in Example 1, and then (Y A )The same separation and drying operations were performed to obtain polyethylene powder (L).

[0397] (Comparative Example 3)

[0398] <(13) Polymerization of polyethylene powder (M)>

[0399] The polymerization catalyst was set to the above-mentioned Ziegler-Natta catalyst (B), the flow rate of n-hexane was set to 40 L / hour, the production rate was set to 13.1 kg / hour, the amount of hydrogen added was set to 13 mol%, the polymerization temperature was set to 83°C, the polymerization pressure was set to 0.37 MPaG, the average residence time was set to 3 hours, the pressure of the final flash tank was set to 0.05 MPaG, and 1-butene was not supplied to the final flash tank. Except for this, polymerization was carried out under the same conditions as Example 4.

[0400] The obtained polyethylene powder (M) had a viscosity average molecular weight of 310,000 and a density of 953 kg / m 3 , the median particle size is 94μm.

[0401] The polymerization activity in the reactor was 41,900 g per 1 g of the catalyst. Table 1 shows the results of the various evaluations performed on the polyethylene powder (M) and the microporous membrane of the polyethylene powder (M) produced by the above (Process for producing microporous membrane).

[0402]

[0403] This application is based on the Japanese patent application (Japanese Patent Application No. 2020-191016) filed with the Japan Patent Office on November 17, 2020, the contents of which are incorporated into this application as a reference.

[0404] Industrial Applicability

[0405] The polyethylene powder of the present invention has industrial applicability as a raw material for various molded bodies, microporous films, and battery separators.

Claims

1. A polyethylene powder having a viscosity average molecular weight of 100,000 or more and 2,500,000 or less, wherein: In the torque curve obtained when mixing was performed using a laboratory mixing extruder under the following <mixing conditions>, The slope of the straight line connecting the two maximum points is greater than 2 N·m / min and less than 12.1 N·m / min. <Mixing conditions> Using a laboratory mixing extruder mixer manufactured by Toyo Seiki Co., Ltd. (main body model: 30C150, mixer model: R-60), 24g of liquid paraffin was mixed for 10 minutes at a set temperature of 114°C and a rotation speed of 5rpm, then 16g of the polyethylene powder and 0.4g of an antioxidant were added, the rotation speed was adjusted to 30rpm and mixed for 3 minutes, and then the set temperature was raised from 114°C to 163°C in 1 minute; after the temperature was raised, mixing was performed for 5 minutes at a set temperature of 163°C and a rotation speed of 30rpm.

2. The polyethylene powder according to claim 1, wherein The polyethylene powder has a viscosity average molecular weight of 200,000 or more and 2,000,000 or less.

3. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has a viscosity average molecular weight of 250,000 or more and 1,200,000 or less.

4. The polyethylene powder according to claim 1, wherein The polyethylene powder has a viscosity average molecular weight of 500,000 or more and 2,500,000 or less.

5. The polyethylene powder according to claim 4, wherein The polyethylene powder has a viscosity average molecular weight of 500,000 or more and 1,500,000 or less.

6. The polyethylene powder according to claim 1 or 2, wherein: In the torque curve, the slope of a straight line connecting two maximum points is 3 N·m / min or more and 12 N·m / min or less.

7. The polyethylene powder according to claim 1 or 2, wherein: In the torque curve, the slope of a straight line connecting two maximum points is 5 N·m / min or more and 10 N·m / min or less. 8 . The polyethylene powder according to claim 1 , wherein the two maximum points are a maximum point in a first peak and a maximum point in a second peak in the torque curve.

9. The polyethylene powder according to claim 1 or 2, wherein: In the torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder, Mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.

3.

10. The polyethylene powder according to claim 9, wherein In the torque curve, the mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.

2.

11. The polyethylene powder according to claim 9, wherein In the torque curve, the mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.

14.

12. The polyethylene powder according to claim 1 or 2, wherein: In the torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder, The mixing energy (E0) at the beginning of swelling is the total mixing energy (E t ) is less than 5%.

13. The polyethylene powder according to claim 12, wherein In the torque curve, the mixing energy (E0) at the beginning of swelling is the total mixing energy (E t ) is less than 1%.

14. The polyethylene powder according to claim 12, wherein In the torque curve, the mixing energy (E0) at the beginning of swelling is the total mixing energy (E t ) is less than 0.1%.

15. The polyethylene powder according to claim 1 or 2, wherein: In the torque curve obtained when kneading is performed under the <kneading conditions> using the laboratory kneading extruder, Mixing energy during swelling (E A ) and the mixing energy during melting (E B ) ratio (E A / E B ) is greater than or equal to 0.02 and less than or equal to 0.

1.

16. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has a median particle size of 50 μm or more and 250 μm or less.

17. The polyethylene powder according to claim 16, wherein The polyethylene powder has a median particle size of 60 μm or more and 200 μm or less.

18. The polyethylene powder according to claim 16, wherein The polyethylene powder has a median particle size of 70 μm or more and 150 μm or less.

19. The polyethylene powder according to claim 1 or 2, wherein: The density of the polyethylene powder is 920 kg / m 3 Above and 960kg / m 3 the following.

20. The polyethylene powder according to claim 19, wherein The density of the polyethylene powder is 930 kg / m 3 Above and 955kg / m 3 the following.

21. The polyethylene powder according to claim 19, wherein The density of the polyethylene powder is 935 kg / m 3 Above and 950kg / m 3 the following.

22. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is composed of ethylene polymers.

23. The polyethylene powder according to claim 22, wherein The ethylene-based polymer is an ethylene homopolymer or a copolymer of ethylene and other comonomers copolymerizable with ethylene.

24. The polyethylene powder according to claim 23, wherein The other comonomers are one or more selected from the group consisting of α-olefins, vinyl compounds and non-conjugated polyenes.

25. The polyethylene powder according to claim 24, wherein The α-olefin is an α-olefin having 3 to 20 carbon atoms.

26. The polyethylene powder according to claim 24 or 25, wherein The α-olefin is propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene or 1-tetradecene.

27. The polyethylene powder of claim 24, wherein: The vinyl compound is vinylcyclohexane or styrene.

28. The polyethylene powder of claim 24, wherein: The non-conjugated polyene is 1,5-hexadiene or 1,7-octadiene.

29. The polyethylene powder of claim 24, wherein: The other comonomers are propylene and / or 1-butene.

30. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is used for a battery separator.

31. The method for producing a polyethylene powder according to any one of claims 1 to 29, wherein The polymerization method of ethylene satisfies one or more of the following three conditions: <Condition 1> The method comprises a multi-step polymerization process, wherein the multi-step polymerization process satisfies the formula (I): (temperature of the last reactor) - (temperature of the first reactor) ≥ 20°C; <Condition 2> The method comprises a multi-step polymerization process, wherein the multi-step polymerization process satisfies the formula (I): (temperature of the last reactor) - (temperature of the first reactor) ≥ 20°C, and copolymerizing the comonomer in a flash tank located between the reactors; <Condition 3> The method comprises the following steps: introducing comonomers into a flash tank located after the reactor, and then polymerizing to obtain an ethylene copolymer.

32. A molded body, wherein The molded body is a molded body of the polyethylene powder according to any one of claims 1 to 29.

33. The shaped body of claim 32, which is a microporous membrane.

34. The molded body according to claim 33, wherein the number of defects in the microporous membrane is less than 5 / (250 mm x 250 mm).

35. The formed article of claim 33, wherein the microporous membrane has a shutdown temperature of less than 134°C.

36. The molded article according to any one of claims 32 to 35, wherein The molded body is a battery separator.

37. The molded article according to claim 36, wherein The battery separator is a separator for lithium-ion secondary batteries.

38. The molded article according to claim 36, wherein The battery separator is a lead-acid battery separator.

39. The method for producing a molded product according to any one of claims 32 to 38, wherein The method for producing the molded body includes the steps of extruding a resin using a wet extrusion method, stretching, extracting, and drying.

Citation Information

Patent Citations

  • PROCESS FOR THE PRODUCTION OF POLYOLEFINS AND THEIR COPOLYMERISATS

    DE3127133A1

  • Ac / dc conversion station

    JP1982022305A

  • Steam treating apparatus of block like fiber

    JP1982082558A

  • Metal ion source

    JP1983040743A

  • Transfer system of incoming call

    JP1986035665A